Disabling or limiting the accession of a shareholder’s heir into a limited liability company – selected issues - Suliński, Grzegorz (Studia Iuridica Toruniensia, 2021)
A limited liability company, as a legal person, continues its legal exist- ence regardless of the fate of its shareholders. In particular, the death of a shareholder does not, in principle, constitute a reason for dissolving the company and, consequently, ending its business activities. A shareholder may also specify the group of persons who will assume the corporate rights and duties in the event of his death. The tools enabling such an indication are found both in the provisions of the Civil Code and the Code of Commercial Companies. In addition to specifying the order of succession through the preparation of a will, the partners may also include a clause in the articles of association disabling or limiting the accession of their heirs into the company. The shareholders are responsible for regulating the exclusion or limitation of succession. The contractual clause regarding this matter should specify the rules of conduct with shares that have been disabled from the succession precisely and in detail. The failure to satisfy this postulate gives rise to significant difficulties of interpretation, raising doubts as to the effect of such a clause. This effect depends especially on the type of restriction on the heir’s accession into the company. Legislative intervention in the wording of the provision of Article 183 of the Code of Commercial Companies should be considered by increasing the requirements regarding the wording of the clause disabling or limiting the accession of heirs to the company in order to specify the method of conduct when acquiring shares in the company with respect to which the articles of association disable inheritance.